Clodronate-Loaded Liposome Treatment Has Site-Specific Skeletal Effects. (April 2019) - Michalski, M.N.; Zweifler, L.E.; Sinder, B.P.; Koh, A.J.; Yamashita, J.; Roca, H.; McCauley, L.K.
Ineffective oral wound healing is detrimental to patients' oral health–related quality of life. Delineating the cellular mechanisms involved in optimal healing will elicit better approaches to treating patients with compromised healing. Osteal macrophages have recently emerged as important positive regulators of bone turnover. The contributions of macrophages to long bone healing have been studied, but their role in oral osseous wound healing following tooth extraction is less clear. Clodronate-loaded liposomes were used as a tool to deplete macrophages in C57BL/6J mice and assess oral osseous bone fill after extraction. In addition to macrophage ablation, osteoclast ablation occurred. Interestingly, depletion of macrophages and osteoclasts via clodronate treatment had differential effects based on skeletal location. In the nonwounded tibiae, clodronate treatment significantly increased CD68+ cells and decreased F4/80+ cells in the marrow, which correlated with increased trabecular bone volume fraction after 7 and 14 d. Serum formation and resorptive markers P1NP and TRAcP 5b were decreased as were tibial TRAP+ osteoclasts. In healing extraction sockets, clodronate treatment increased extraction socket trabecular bone thickness at 14 d, which correlated with decreased TRAP+ osteoclasts and F4/80+ macrophages. Conversely, nonwounded maxillary interseptal bone was unaffected by clodronate treatment. Furthermore, the increase in extraction socket bone fill with clodronate was less than the large increase in trabecular bone observed in a nonwounded long bone. These data suggest a temporal and spatial specificity in the roles of macrophages and osteoclasts in normal turnover and healing.